“The Moon and Sixpence” by S. Maugham as a “Hidden” Prototext of J. Fowles’s Short Story “The Ebony Tower” - Bilyk, Natalia (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2025)
Maugham’s "The Moon and Sixpence" is first considered as a prototext of Fowles’s "The Ebony Tower". It’s presence is not emphasised by quotations, proper names or other types of markers aimed at its actualisation in the process of reading, but by less obvious markers (conventions of а genre, motifs etc.) that are not so easy to read; this allows us to speak of a "hidden" prototext. The goal of the research is to reveal Maugham’s novel as a prototext for "The Ebony Tower" and to demonstrate its functioning in this role. The article presents arguments for the presence of "The Moon and Sixpence" as a prototext for "The Ebony Tower", demonstrates the forms of this presence and its functioning. It has been shown that the character of Henry Breasley is typologicaly similar to the protagonists of the Künstlerroman characteristic of the first half of the 20-th century. Fowles’s purposeful attention to Maugham’s novel is evidenced by the similarities to it found at different poetic levels of "The Ebony Tower", but first of all by Fowles’s emphasis on the vitality power in Breasley, which forms the essence of Maugham’s conception of an artist and art. The final short story of the collection, "Enigma", contains allusions to the turning point of Maugham’s novel (disappearance); it is included in the analysis because the works in Fowles’s collection are interconnected. The research provides arguments for the assertion that Fowles purposefully involved Maugham’s novel in the creation of "The Ebony Tower", especially in modelling the character of Henry Breasley. There is every reason to assume that the decisive factor in the selection of this prototext might be the powerful vitality embodied by Maugham in Strickland and interpreted as the source of his art; the same position Breasley takes in the debate with David Williams. The absence of explicit references to "The Moon and Sixpence" in Fowles’s short story leads to the conclusion that their avoidance was part of the writer’s strategy of working with the prototext.